CNV-Z; a new tool for detecting copy number variation in next generation sequencing data - Emma Adolfsson; Jon Jonasson; Aniruddh Kashyap; Anna Nordensköld; Anna Greén (SoftwareX, 2023)
We developed an efficient approach to diagnostic copy number analysis of targeted gene panel or whole exome sequence (WES) data. Here we present CNV-Z as a new tool for detection of copy number variants (CNVs). Deletions and duplications of chromosomal regions are widely implicated in both genomic evolution and genetic disorders. However, calling CNVs from targeted or exome sequence data is challenging. In most cases, the copy number of a chromosomal region is estimated as the depth of reads mapping to a certain bin or sliding window divided by the expected number of reads derived from a set of reference samples. This approach will inevitably miss smaller CNVs on an irregular basis, and quite frequently results in a disturbing number of false positive CNVs.We developed an alternative approach to detect CNVs based on deviation from expected read depth per position, instead of region. Cautiously used, the cohort of samples in the same run will do as a reference. With appropriate filtering, given high quality DNA and a set of suitable reference samples, CNV-Z detects CNVs ranging in length from one nucleotide to an entire chromosome, with few false positives. Performance is proved by benchmarking using both in-house targeted gene panel NGS data and a publicly available NGS dataset, both sets with multiplex ligation-dependent amplification probe (MLPA) validated CNVs. The outcome shows that CNV-Z detects single- and multi-exonic CNVs with high specificity and sensitivity using different kind of NGS data. On gene level, CNV-Z shows both excellent sensitivity and specificity. Compared to competing CNV callers, CNV-Z shows higher specificity and positive predictive value for detecting exonic CNVs.